2001
DOI: 10.1080/01140671.2001.9514167
|View full text |Cite
|
Sign up to set email alerts
|

Flower quality and fruit size in kiwifruit (Actinidia deliciosa)

Abstract: Kiwifruit (Actinidia deliciosa (A. Chev.) C.F. Liang et A.R, Ferguson 'Hayward') vines were grown at five sites that represented the climatic range of the major kiwifruit growing regions of New Zealand. Hydrogen cyanamide was applied to half the vines at three of the sites. Measurements of flower quality over two seasons were used to determine if this was linked to fruit weight at harvest. There was a progressive increase in ovary fresh weight and ovary dry weight from warmer to cooler sites. Hydrogen cyanamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…chinensis and A. eriantha [53]. Cytokinin concentrations were also elevated in 'Zesy002' fruit in this study during early fruit development (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) suggesting that cell division in this genotype occurred during the very early stages of kiwifruit growth [54] before treatments were applied. Therefore increases in fruit growth through high carbohydrate source supply to fruit sinks in this study were likely due to increased cell expansion [55].…”
Section: The Effect Of Carbohydrate Source Manipulation On Fruit Growthmentioning
confidence: 53%
“…chinensis and A. eriantha [53]. Cytokinin concentrations were also elevated in 'Zesy002' fruit in this study during early fruit development (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) suggesting that cell division in this genotype occurred during the very early stages of kiwifruit growth [54] before treatments were applied. Therefore increases in fruit growth through high carbohydrate source supply to fruit sinks in this study were likely due to increased cell expansion [55].…”
Section: The Effect Of Carbohydrate Source Manipulation On Fruit Growthmentioning
confidence: 53%
“…In cases where we obtained negative values for pollination deficit, we considered that these indicate the absence of pollination deficit and were treated as zero in subsequent calculations in this study. Despite our attempts to minimize them, negative values may result from within individual differences (e.g., ovary size, resource allocation, shadow) known to affect fruit weight within plants [ 51 , 52 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Austin et al (1999) described a similar correlation between early cell division and final fruit size in apple, but they cautioned that this linkage may not be causal. McPherson et al (2001) suggested that fruit size potential of kiwifruit may be determined even earlier in the season, between budbreak and flowering. They attempted to link fruit size at harvest to flower ovary weight at mid bloom.…”
Section: Fruit Size Potentialmentioning
confidence: 99%
“…The maximum fruit size potential of kiwifruit is believed to be determined early in development, either before flowering (Piller et al 1998;McPherson et al 2001) or during an early stage of cell division (Austin et al 1999). Hall et al (1996) reported that c. 75% of the variation in mean fruit volume at harvest was already determined by 50 days after flowering.…”
Section: Introductionmentioning
confidence: 99%